K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

2 tháng 5 2020

\(\frac{-2}{3}=\frac{x}{-6}=\frac{10}{-y}=\frac{z}{9}\)

\(\frac{-2}{3}=\frac{x}{-6}\Rightarrow\left(-2\right)\left(-6\right)=3x\Rightarrow12=3x\Rightarrow x=4\)

\(\frac{4}{-6}=\frac{10}{-y}\Rightarrow-4y=-60\Rightarrow y=15\Rightarrow-y=-15\)

\(\frac{10}{-15}=\frac{z}{9}\Rightarrow-15z=90\Rightarrow z=-6\)

\(\frac{-2}{3}=\frac{x}{-6}=\frac{10}{-y}=\frac{z}{9}\)

\(\frac{-2}{3}=\frac{x}{-6}\Leftrightarrow\frac{4}{-6}=\frac{x}{-6}\Leftrightarrow x=4\)

\(\frac{4}{-6}=\frac{10}{-y}\Leftrightarrow4y=-60\Leftrightarrow y=-15\)

\(\frac{10}{15}=\frac{z}{9}\Leftrightarrow\frac{90}{135}=\frac{15z}{135}\Leftrightarrow15z=90\Leftrightarrow z=6\)

19 tháng 3 2022

y x 23,2 + y x 9,8=755,7